A Discourse Analysis of Humour & Incongruity in Chinua Achebe’s “A Man of the People” - Sharif, Qaisar; Naseem, Shazia (Pakistan Languages and Humanities Review, 2025)
This paper analyzes how humor is constructed and functions thematically in “A Man of the People” by “Chinua Achebe”. Veatch states that two incongruous elements form humor, the first one is the violation of ‘subjective moral order’ and the other is socially normal. Considering Veatch’s principles about incongruity, several examples containing congruent and incongruent elements are foregrounded in this paper. Humor as well as its attachment and detachment with somebody or something, characters’ attitude, and the conditions in which humorous make-up is established along with others, is to be explained. The study finds that humor based on incongruity increases reader engagement while highlighting broader societal faults. Future research should look at comparative humorous methods in African postcolonial literature to better understand the role of humor in sociopolitical commentary.